Pengaruh Pertumbuhan Penjualan, Exchange Rate, Modal Kerja Dan Likuiditas Terhadap Pertumbuhan Laba Pada Pt. Super Power Technology - Vinniesya Vinniesya; Thomas Sumarsan Goh; Elidawati Elidawati; Edison Sagala (Economics and Digital Business Review, 2023)
Super Power Technology is a Bantex distributor company which is a brand of books, receipts, maps. PT. Super Power also explores various things related to stationery and computers. PT. Super Power is located at Jalan Hindia No. 88C Medan. Good profit growth indicates that the company has good finances, which in turn will increase the value of the company. Factors that influence profit growth are sales growth, exchange rate, working capital and liquidity. The purpose of this study was to determine the effect of Sales Growth, Exchange Rate, Working Capital and Liquidity on Profit Growth at PT Super Power Technology. The method used is quantitative research. Data collection techniques used are documentation techniques and secondary data collection from the financial statements of PT Super Power Technology. The population in this study is the financial statements of PT Super Power Technology, while the sample financial statements are 3 years for the 2018-2020 research period. The analysis model in this study is multiple linear regression using the SPSS program. Testing the data is done by classical assumption test, coefficient of determination test, F test and t test. The conclusion from the results of this study is that sales growth and liquidity affect profit growth, while the exchange rate and working capital have no effect on profit growth at PT Super Power Technology. Sales growth, exchange rate, working capital and liquidity simultaneously affect profit growth at PT Super Power Technology Medan with a coefficient of determination of 0.824, which means that 82.4% of profit growth variables can be explained by variables of sales growth, exchange rate, working capital and liquidity. and the remaining 17.6% is varied by other factors not examined such as inventory, fixed assets, total assets and so on